Fundamentals of Evidence Based Medicine - Prasad, Kameshwar; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
This is a basic book on evidence-based medicine (EBM). It starts with an introduction to the topic. It outlines the relationship between EBM and research and quality of care. Then It goes on to cover the most commonly used modules of EBM, i.e. therapy, diagnosis, prognosis and meta-analysis. Each module starts with an introduction to fundamental concepts, and description of the related research process, and then follows the critical appraisal of related type of research artcle. At the end, it covers the different systems of grading of level of evidence and strength of recommendations. The book also has three examples of critical appraisal on diagnosis, therapy, and meta-analysis.
Chapter 1.Introduction to evidence-based medicine -- Chapter 2.Finding the current best evidence -- Chapter 3.Therapy:fundamental concepts -- Chapter 4.Therapy:critical appraisal-part 1 (validity) -- Chapter 5.Therapy:critical appraisal- part 2 (interpreting results) -- Chapter 6.Diagnostic test: Fundamental concepts -- Chapter 7.Diagnostic test: Critical appraisal -- Chapter 8.What is the information? (How to evaluate the results if a diagnostic test paper) -- Chapter 9.Systematic review and meta analysis: fundamental concepts -- Chapter 10.Meta -analysis: critical appraisal -- Chapter 11.Prognosis -- Chapter 12.Examples of critical appraisal.
Keywords: Medicine; Internal medicine; Nursing administration; Dentistry; Nursing—Research.; Medicine/Public Health, general; Internal Medicine; Nursing Management; Dentistry; Nursing Research